KUALITAS PELAYANAN BAGI KEPUASAN KONSUMEN PEMBELI RUMAH GRAND CITY BALIKPAPAN - Maryanti Maryanti; Casmudi Casmudi; Ashari Sofyaun (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2018)
Serve is a part of action/service for others to be able to meet the needs and desires. Customers satisfaction might be checked by comparing the expectations of consumers with the desired quality of service what they receive in fact. This research was conducted to find out how customer satisfaction with the quality of service the management of Grand City Balikpapan. Research used qualitative methods. Data sources are secondary and primary data. Data collection techniques through interviews, observation, documentation and triangulation. Data collection instruments through the interview grid with the 5W + 1H method. The validity of the data was examined through triangulation and data analysis techniques using data reduction, data display and drawing conclusions or verification (conlusion drawing / verification). Finally Grand City Balikpapan consumers have been satisfied with the quality of service provided by the Sinarmas Land Group management.